HUBUNGAN CITRA TUBUH, AKTIVITAS FISIK, DAN PENGETAHUAN GIZI SEIMBANG DENGAN IMT/U PADA REMAJA PUTRI SMA NEGERI DI KECAMATAN SETIABUDI JAKARTA SELATAN TAHUN 2022 - Agista Khairul Jannah (2022)
Adolescence is a period of transition from child to adult. The physical growth of adolescents is very rapid, especially young women. The prevalence of nutritional status of adolescents aged 16-18 years as much as 8.1% experienced less nutritional status and 13.5% over nutritional status. Adolescents are vulnerable to nutritional problems due to increased nutritional needs along with growth. Indicators of measuring a person's nutritional status are related to Body Mass Index (BMI) and Age (U) in determining the category of nutritional status. Several indirect causes of nutritional status imbalance are body image, physical activity, and knowledge of balanced nutrition. The purpose of this study was to determine the relationship between body image, physical activity and knowledge of balanced nutrition with BMI/U in female high school students in Setiabudi sub-district, South Jakarta in 2022. This research method used a quantitative approach with a cross-sectional design. The sample of this research is 102 respondents using stratified random sampling technique. Data analysis in this study used the Pearson correlation statistical test. The results of bivariate data analysis showed that there was a relationship between body image (p=0.000) and physical activity (p=0.004) with BMI/U and there was no relationship between knowledge of balanced nutrition (p=0.831) and BMI/U in female senior high school students. in Setiabudi sub-district, South Jakarta in 2022. It is expected that young women have a positive body image perception, routinely do physical activity, and broaden their horizons about balanced nutrition. Keyword : Body Image, Physical Activity, Knowledge of Balanced Nutrition, BMI/U